Basic microsurgery training. Center for Experimental Surgery, "Victoria de Girón" Institute of Basic and Pre-Clinical Sciences - Víctor Manuel Rodríguez Sosa; Heberto Arides Domínguez López; Iriana Zubizarreta Hernández; Adrián Gutiérrez González; Yilenis Aliaga Aliaga (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: Microsurgical techniques are currently applied in different surgical specialties worldwide. During the 90´s, our center began to implement vascular and nerve microsurgery trainings to specialists and national and foreign residents, respectively.  Objective: To evaluate the results of microsurgery training that it is taught in the Center for Experimental Surgery at "Victoria de Girón" Institute of Basic and Pre-Clinical Sciences. Material and methods: A retrospective longitudinal study was carried out to evaluate the microsurgery training program. The training was divided into three main parts:  theoretical lessons; practices upon the latex simulator; end-to-end anastomosis of small intestine on the rat; and finally, the development of basic microsurgical techniques on different vascular structures (abdominal aorta and vein) and the sciatic nerve of the rat, for a total of 90 hours of training.  The total enrollment during the mentioned period was 203 students to whom a survey was applied at the end of the training; also, the time of realization of anastomosis and the vascular permeability were measured and evaluated as Bad, Good, and Excellent. Results: The results were satisfactory in general, but 90% of students that were carrying out their studies of a surgical specialty showed better skills in a shorter period than those that didn't practice surgery, demonstrating a less time-consuming exercise in the realization of vessel anastomosis and obtaining a good vascular permeability in this group. Conclusions: This teaching method constitutes a useful tool so that the students develop the necessary skills to carry out microsurgical practices in clinical surgery successfully. Keywords: Microsurgery, microsurgical training, microsurgical teaching method, microsurgical techniques, vascular microsuture, nervous microsuture, end-to-end microsutute.